Perancangan Interior Sekolah Tinggi Seni di Surabaya - Merry Wulandari; mariana wibowo (Intra, 2014)
Art has now become an aspect of entertainment at this moment and has been a lifestyle for the people of Indonesia. Most of the Indonesians are enjoying art as entertainments for their everyday lives. Music, dance, fine arts, drama are a few examples of arts. With more and more communities are enjoying such arts, Indonesia has really appreciates art very much. Therefore, there is an idea of creating Performing Arts School here in Surabaya. The Performing Arts Scool will then facilitate students with a place to stay within the school. With the system of dormitory, students will be able to live nearby and ease them to study. The design of the Performing Arts School is following the modern retro style, adjusting with the target segment and that is students between the ages of 18 – 25 years old. This age range is the range where students are more interested with something that is contrast and catching attention. Interiors that are using bright colors and geometric style allows students to stimulate their creativity.